Piano in a factory [videorecording (DVD)] = Gang de qin - Zhang, Meng, 1975-; Wang, Qianyuan, 1972-; Qin, Hailu; Chang, Sin-yŏng (Film Movement series, 2011)
"When Chen's estranged wife reappears asking for a divorce and custody of their daughter, the musician girl decides she will live with whoever can provide her with a piano. Chen's struggle thus begins. When efforts to borrow money and even steal a piano fail, Chen concocts a preposterous plan - he'll make a piano from scratch! He persuades a bunch of reluctant, but loyal, misfit friends to help him forge the instrument in a derelict factory from a heap of scrap steel. Though crude in design and tune, the factory piano awaits its first and final performance from his little girl."--Container.